TEORI-TEORI BELAJAR DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA - Ahmad, Idrus; Djais, Idwan (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
Learning theories are considered to have opened the veil on language learning, both first and second languages. The learning theories that are the object of this study are the Nativism theory pioneered by Noam Chomsky, the Behaviorism theory pioneered by John B. Watson, the Cognitivism theory, and the Constructivism theory pioneered by Jean Piaget, which are very influential in language learning. Two controversial theoretical views from America, namely the theory of nativism and behaviorism. Nativism theory argues that language mastery is natural. Meanwhile, behaviorism theory argues that language mastery is "nurture". This is different from the view of cognitivism theory that language learning is largely determined by a person's reasoning or thinking ability. Learning a language is a complex thinking process that continues to develop between cognitive levels and the language environment. Meanwhile, constructivism theory holds that language learning occurs according to a certain pattern of developmental stages according to age. These stages include assimilation, accommodation, disquilibration and equilibration. Language learning must be actively constructed by the child rather than explained in detail by others. Starting from this basic theory, this article aims to explain how this learning theory is implemented in language learning. It is hoped that this will result in language learning that is effective and easy to understand for students who are learning a language.